Integration of Biosensors and Associated Electronics on Lab-on-Chip Devices - Giannitsis, A. T.; Parve, T.; Min, M. (Elektronika ir Elektrotechnika, 2011)
Lab-on-chip devices comprise a class of bioelectronic miniaturized devices that incorporate microfluidic and biosensing apparatuses on a single chip. They are dedicated for analyzing and processing biochemical liquid samples, which may consist of enzymes, proteins, nucleotides, or even cells and viruses. Furthermore, lab-on-chips may enhance synthesis of biochemical products. The importance of lab-on-chip devices lies on their potentiality of advancing the development of environmental monitoring sensors and also point-of-care analyzers in medicine. This article presents the usual microfabrication methods for manufacturing lab-on-chip devices, with emphasis on the integration of the biosensor, the biocompatibility of the sensing element of the biosensor, and the essential electronics. Three major types of biosensors are analyzed: optical, impedimetric and electrochemical ones. Ill. 7, bibl. 28 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.110.4.288